1998
DOI: 10.1007/s001250051062
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in Type II (non-insulin-dependent) diabetes: evidence of a role for neuropathy and a protective effect of HLA-DR4

Abstract: The prognosis of patients with Type II (non-insulindependent) diabetes mellitus is primarily determined by the presence of macro-and microangiopathy. There is, however, a large variation in the propensity for the patient to develop these devastating complications. While poor glycaemic control and duration of diabetes are strong predictors of microangiopathy [1], their role as predictors of macroangiopathy is less clear [2±6]. In Type II diabetes, clustering of the metabolic syndrome (hyperglycaemia, obesity, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 44 publications
2
81
1
7
Order By: Relevance
“…Family history of type 1 diabetes was negatively associated with coronary artery disease in relatively young (Ͻ60 years of age) type 2 diabetic patients, and patients with such family history were leaner than those with family history for type 2 diabetes only (24). Also, type 2 diabetic patients with the type 1-associated HLA-DR4 allele had a lower cardiovascular mortality rate than DR4 Ϫ patients (25). Overall, the patients with mixed family history also had lower serum C-peptide concentrations, but this largely depended on the high frequency of circulating autoantibodies to GAD (GADAs) in this group, whereas the BMI and coronary artery disease association was present also in GADA Ϫ patients (24).…”
Section: Phenotypic Consequences Of the Familial Clusteringmentioning
confidence: 93%
“…Family history of type 1 diabetes was negatively associated with coronary artery disease in relatively young (Ͻ60 years of age) type 2 diabetic patients, and patients with such family history were leaner than those with family history for type 2 diabetes only (24). Also, type 2 diabetic patients with the type 1-associated HLA-DR4 allele had a lower cardiovascular mortality rate than DR4 Ϫ patients (25). Overall, the patients with mixed family history also had lower serum C-peptide concentrations, but this largely depended on the high frequency of circulating autoantibodies to GAD (GADAs) in this group, whereas the BMI and coronary artery disease association was present also in GADA Ϫ patients (24).…”
Section: Phenotypic Consequences Of the Familial Clusteringmentioning
confidence: 93%
“…While there is evidence that this is true [45], it is difficult to dissect an effect of distal symmetrical neuropathy from a possible confounding effect on mortality from autonomic neuropathy and cardiac denervation [46], as well as from the effect of nephropathy. Given, however, that the vascular calcification associated with neuropathy would be characterised by widened pulse pressure, it is worth noting that widened pulse pressure has recently been shown to be an independent predictor of death in patients with renal failure [47,48].…”
Section: Diabetic Neuropathy and Cardiovascular Riskmentioning
confidence: 99%
“…Finally, it was recently demonstrated that elevated NEFA levels predict CVD mortality in patients with type 2 diabetes. 34 The question remains of how high NEFA concentrations could promote CVD. High levels of NEFA could lead to increased concentrations of VLDL, small, dense LDL particles, and elevated apoB concentrations in plasma, all of which are associated with an increased risk of coronary heart disease 32 and stroke.…”
Section: Carlsson Et Al Nonesterified Fatty Acids and Familial Cvdmentioning
confidence: 99%
“…Support for this view comes from a recent prospective study showing elevated NEFA concentrations 10 years earlier in patients with type 2 diabetes who died of CVD. 34 …”
Section: Carlsson Et Al Nonesterified Fatty Acids and Familial Cvdmentioning
confidence: 99%